Effects of AI Chatbots on Customer Satisfaction: Understanding the Mediating Role of Customer Satisfaction on Customer Loyalty - Ali, Imran; Naushad, Mohammad; Faridi, Mohammad Rishad; Rashed, Abdullah Saad (International Review of Management and Marketing, 2026)
Advanced chatbots are powered by artificial intelligence, capable of solving complex queries, communicating with customers, and providing instant services through messaging. Advanced chatbots are not limited to customer support services, consumer research and recommendations. AI chatbots are used across industries like banking, financial services, hotel, tourism, media and entertainment and education. This is the need of the hour to assess the impact of AI chatbots on customer satisfaction and customer loyalty. The primary objective of this study is to determine the impact of AI chatbots on customer satisfaction and loyalty. This topic is considered for the research since artificial intelligence is influencing each business and individual. The current study considered one dependent variable (customer loyalty), and one mediating variable (customer satisfaction) and four independent variables (usability, responsiveness, trust and perceived risk). The sampling technique used for data collection was convenience sampling and the sample size was 413. Statistical techniques like exploratory factor analysis (EFA), structural equation modeling (SEM), and mediation analysis were used for data analysis. All construct of this study meets the threshold with average variance extracted exceeding 0.50 and composite reliability exceeding 0.70. All indices of the model fit were found statistically significant on several parameters. Among all variables, only perceived risk affects the customer satisfaction.